Analytical and Clinical Performance Evaluation of ARK Fentanyl II Assay on Beckman Coulter AU System. (28th October 2021) - Larsen, N; Smothers, C; Martin, D; Moore, A; Lima, J; Cao, L
Abstract: Introduction/Objective: Drugs of abuse, specifically opioids, have been in recent years an important focus in both medicine and media due to the 'opioid epidemic' and large numbers of overdose deaths. Synthetic opioids such as fentanyl have contributed to this epidemic. The CDC reports that of roughly 50, 000 opioid overdose deaths in 2019, nearly 73% were due to synthetic opioids. The objective of this study is to assess the analytical and clinical performance of the Fentanyl II Assay by ARK Diagnostics, Inc. Methods/Case Report: Fentanyl was qualitatively determined by the ARK Fentanyl II Assay, a homogenous enzyme immunoassay based on competition between drug in the specimen and drug labeled with recombinant glucose-6- phosphate dehydrogenase (rG6PDH) for antibody binding sites. The presence of drug in urine increases enzyme activity, which converts nicotinamide adenine dinucleotide (NAD) to NADH in the presence of glucose-6-phosphate, resulting in an absorbance change measured by spectrophotometry. The evaluation was performed following CLSI guidelines. The analytical performance was evaluated for accuracy and precision. Results (if a Case Study enter NA): To evaluate the accuracy, twelve positive and eight negative specimens were tested by the ARK immunoassay performed on two Beckman Coulter instruments (AU480 and AU680) and by LC- MS/MS. The results from both instruments showed 100% agreement with the results from LC-MS/MS. On instrument AU480, the within-run CVs were 18.0% at the level of 22.510 ng/mL and 0.8% at the level of 552.628 ng/mL. The between-run CVs were 8.8% at the level of 68.928 ng/mL and 3.7% at the level of 158.947 ng/mL. On instrument AU680, the within-run CVs were 273.4% at the level of 1.052 ng/mL and 0.8% at the level of 523.788 ng/mL. The between-run CVs were 7.8% at the level of 53.779 ng/mL and 3.1% at the level of 145.263 ng/mL. In May 2021, 2, 075 fentanyl assays were run at UAB. Of those, 476 returned a positive result with a positive rate of 22.9%, and 1, 599 were negative with a negative rate of 77.1%. One positive result was confirmed by LC-MS/MS as negative for fentanyl but positive for norfentanyl, a metabolite of fentanyl. The clinical specificity was 99.9% and sensitivity was 100%. Conclusion: In Conclusion, the ARK fentanyl Assay II on Beckman Coulter AU system has good accuracy, sensitivity and specificity. The precision at medium and high levels are good. However, the precision at low level needs to be improved.